Principal Leadership Strategies in Managing the Implementation of Education Management Information Systems in Nature Schools - Linda Haerunnisa; Mada Sutapa (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
Digital transformation in education positions school principals as strategic actors in managing the implementation of the Education Management Information System (EMIS); however, empirical studies remain concentrated on formal schools and have not adequately explored alternative school contexts. This study aims to analyze principals' leadership strategies in managing EMIS implementation in nature schools, alternative educational institutions with distinct philosophical, pedagogical, and cultural characteristics. The study employed a qualitative approach with a multiple case study design at two nature schools, Naufal Zahra School and Arrasyid School. Data were collected through semi-structured interviews with two principals as key informants and four supporting informants (teachers and system operators), participant observation, and documentary analysis. Data analysis followed the Miles, Huberman, and Saldaña interactive model encompassing data condensation, thematic display, and conclusion drawing and verification, supported by source, method, and cross-case triangulation. The findings identify five mutually reinforcing leadership strategies: needs-diagnostic planning, phased socialization and implementation, differentiated training combined with empowering operators as internal technical agents, institutional digital culture building, and adaptive management of implementation barriers. These strategies improved administrative effectiveness, accelerated data-driven decision-making, and strengthened school–parent communication while maintaining coherence with the humanistic values of nature schools. This study contributes to educational leadership theory by demonstrating that successful EMIS implementation in alternative institutions rests on contextual, transformational, and adaptive leadership strategies attuned to organizational culture.